Investigating the CO2 Emissions Convergence and its Nexus with Growth, Renewable Energy, and Energy Intensity in OIC Countries - Muhammad, Mansur; Audu, Bello; Ibrahim Ahmed, Sadiq (Muslim Business and Economics Review, 2025)
Carbon dioxide (CO₂) emissions pose a significant climate threat, impacting all aspects of human activity and necessitating global collaboration to protect both human and nonhuman species. Transitioning from fossil fuels to renewable energy and enhancing energy efficiency are widely regarded as the most effective strategies for reducing emissions and mitigating global warming. Against this backdrop, we examine CO₂ emissions convergence among 50 Organization of Islamic Countries (OIC) member states, considering the role of economic growth, renewable energy use, and energy intensity. Our analysis employs stochastic, club, and beta convergence methods, alongside system generalized method of moments (GMM) estimation. Four key findings emerge from this analysis. First, accounting for country heterogeneity and cross-sectional dependence, we confirm stochastic convergence in CO₂ emissions among OIC members. Second, there is evidence of club convergence, where emissions cluster into distinct groups. Third, while renewable energy consumption negatively affects emissions pathway, energy intensity positively and directly affects CO₂ emissions’ growth. However, fourth, economic growth increases carbon emissions. These findings have significant policy implications. If emissions do not converge, allocating emission rights through carbon trading could lead to substantial international wealth transfers, influencing global carbon policy. Additionally, countries with similar convergence patterns could adopt common climate policies. At the same time, all nations should prioritize increasing the share of renewable energy in their energy mix to achieve sustainable emission reductions.